1997
DOI: 10.2307/3802140
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Factors Influencing Beaver Dam Establishment in a Northern Ontario Watershed

Abstract: Beaver (Castor canadensis) dam-site selection studies traditionally have relied on plant composition. To understand how habitat factors influence dam establishment, we compared 9 plant composition and size categories and their spatial distribution with 4 physical features at 15 active dams, 15 abandoned dams, and 12 no-dam sites. To establish pre-dam vegetation densities, plots downstream and upstream from impoundments were averaged. We found beaver relied on both physical (upstream watershed area and stream c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 8 publications
2
37
0
Order By: Relevance
“…When 2 outliers (triangles) are removed, the relationship was not significant (r 2 = 0.20, F1,9 = 2.28, P = 0.17). (Allen, 1983;Barnes and Mallik, 1997). Our focal beavers may be occupying territories with non-limiting resources during the period studied.…”
Section: Discussionmentioning
confidence: 99%
“…When 2 outliers (triangles) are removed, the relationship was not significant (r 2 = 0.20, F1,9 = 2.28, P = 0.17). (Allen, 1983;Barnes and Mallik, 1997). Our focal beavers may be occupying territories with non-limiting resources during the period studied.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out on both beaver species European beaver C. fiber and North American beaver Castor canadensis mostly contain only data obtained during one season (Slough and Sadleir 1977;Beier and Barrett 1987;Dieter and McCabe 1989;McComb et al 1990;Robel et al 1993;Hartman 1996; Barnes and Mallik 1997;Suzuki and McComb 1998;Fustec et al 2001;Fustec et al 2003). Howard and Larson (1985), Broschart et al (1989), and Fryxell (2001) have all described habitat selection based on a longer period, however, but the research was conducted in study areas which were already occupied by beavers when the research began.…”
Section: Introductionmentioning
confidence: 97%
“…and Naiman 1990; Barnes and Mallik 1997). I made a careful examination of the area and found that there was no apparent way that Beavers could have cut the stems at such a height.…”
mentioning
confidence: 99%